2023
DOI: 10.3390/su15042860
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Soft Story on the Seismic Response of Non-Structural Components

Abstract: Multi-story, reinforced-concrete (RC) building structures with soft stories are highly vulnerable to damage due to earthquake loads. The soft story causes a significant stiffness irregularity, which has led to numerous buildings collapsing in previous seismic events. In addition to the structural collapse, the failure of non-structural components (NSCs) has also been observed during past earthquakes. In light of this, this study investigates the effect of a soft story and its location on the seismic behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…4, it can be observed that the two peaks observed in the elastic and inelastic FRS are recorded close to the structure's elastic and inelastic modal periods (Table 3), respectively. This finding from this study is consistent with the outcomes of the previous research [11][12][13]. The Floor Response Spectra (FRS) exhibit a consistent trend of increasing magnitude from the first floor at the bottom to the third floor at the top.…”
Section: Floor Response Spectrum (Frs)supporting
confidence: 93%
See 1 more Smart Citation
“…4, it can be observed that the two peaks observed in the elastic and inelastic FRS are recorded close to the structure's elastic and inelastic modal periods (Table 3), respectively. This finding from this study is consistent with the outcomes of the previous research [11][12][13]. The Floor Response Spectra (FRS) exhibit a consistent trend of increasing magnitude from the first floor at the bottom to the third floor at the top.…”
Section: Floor Response Spectrum (Frs)supporting
confidence: 93%
“…The floor response spectrum (FRS) method is an analytical approach that operates by separating various considerations [7][8][9][10][11][12][13]. Initially, the primary structure undergoes dynamic analysis independently, without factoring in the secondary system's influence.…”
Section: Introductionmentioning
confidence: 99%
“…For seismic resilient buildings, the performance of NSEs is important for absorbing earthquake damages [56]. NSEs with a short period attract more earthquake forces when present on the lower floors of the building without any soft story effect [56] The recovery path for a structure in terms of function vs. time as studied in the research by Henry V. Burton et al, 2018 [57], is displayed below in Figure 13. The 2475-year hazard scenario shows no difference between the no utility dependence and the baseline utility dependence [58].…”
Section: Framework For Building Performance In the Assessment Of Comm...mentioning
confidence: 99%
“…Heidari et al, 2020 [54] showed that governments should formulate useful policies to reduce vulnerability and increase resilience. The research of Pesaralanka et al, 2023 [56] is limited to linear analysis only; the damages of NSEs and EAL need to be researched further. Asadi et al, 2019 [28] showed that diagrids have good lateral capacity and can reduce CO 2 emissions, but sufficient knowledge of the construction quality is required.…”
Section: Research Gapmentioning
confidence: 99%
“…For seismic resilient buildings, the performance of NSEs is important for absorbing the earthquake damages [61]. NSE with short period attract more earthquake forces when present in the lower floors of the building without any soft story effect [61] The recovery path for a structure in terms of function vs time can be displayed below in Figure 25: The 2475-year hazard scenario shows no difference between the no utility dependence and the baseline utility dependence [63]. For a retrofit cost of $ 100 (Millions) on a community, the fatalities, CO2 emissions etc.…”
Section: Framework For Building Performance In the Assessment Of Comm...mentioning
confidence: 99%